2019
DOI: 10.1111/cns.13228
|View full text |Cite
|
Sign up to set email alerts
|

Role of the PGE2 receptor subtypes EP1, EP2, and EP3 in repetitive traumatic brain injury

Abstract: Aims The goal was to explore the signaling pathways of PGE2 to investigate therapeutic effects against secondary injuries following TBI. Methods Young (4.9 ± 1.0 months) and aged (20.4 ± 1.4 months) male wild type (WT) C57BL/6 and PGE2 EP1, 2, and 3 receptor knockout mice were selected to either receive sham or repetitive concussive head injury. Immunohistochemistry protocols with Iba1 and GFAP were performed to evaluate microgliosis and astrogliosis in the hippocampus, two critical components of neuroinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…These observations are inconsistent with the ndings where alleviation in expression of NLRP3/NFkB reduced microglial activation and proin ammatory cytokines [84,85]. Both ValS an SC19220 rescued microglial and astrocyte activation as their (COX-1/EP1) predominance in those cells thus ameliorated neurogenic niches perturbations.…”
Section: Discussioncontrasting
confidence: 59%
“…These observations are inconsistent with the ndings where alleviation in expression of NLRP3/NFkB reduced microglial activation and proin ammatory cytokines [84,85]. Both ValS an SC19220 rescued microglial and astrocyte activation as their (COX-1/EP1) predominance in those cells thus ameliorated neurogenic niches perturbations.…”
Section: Discussioncontrasting
confidence: 59%
“…On the other hand, the mammalian TBI model is more advanced in its robust research background focusing on the mechanism and important biomarkers. 117,[163][164][165][166][167][168] In addition to that, non-mammalian research has not conducted any research on inducing stem cell for brain injury as been conducted previously in this study with mammalian model. 169,170 Indeed, one of the study showed successful xenotransplantation of human iPSC-derived NSCs and isogenic neural cell progenies in a mouse model.…”
Section: Future Direction Of Non-mammalian Animal Model In Traumatimentioning
confidence: 98%
“…The research group of Ibarra reveals that immunization with neural derived peptides possesses neurogenic and regenerative properties which render motor and sensitive recovery in the chronic stage of SCI 10 . Such combined targeting of neurogenesis and regeneration may be similarly applied to TBI, since the pathology of TBI manifests with impaired stem cell potencies, as recognized in the cell therapy campaign noted in the other papers described here 5‐7 …”
mentioning
confidence: 92%
“…Recognizing that cell therapy may not be a magic bullet, Willing and co‐workers 7 offer a combination therapy. Here, they show the potential of combining cell therapy with drugs that target signaling pathways of the neuro‐immune‐inflammatory axis.…”
mentioning
confidence: 99%
See 1 more Smart Citation